The effects of improving the mesothelioma surveillance network on sensitivity, timeliness in reporting and asbestos exposure assessment - Mangone, Lucia; Di Felice, Enza; Storchi, Cinzia; Romanelli, Antonio; Broccoli, Serena; Vicentini, Massimo; Giorgi Rossi, Paolo (La Medicina del Lavoro, 2017)
Background: In Italy, Mesothelioma Registries (MRs) have been established by law for the epidemiological surveillance of occupational cancers. MRs collect information about asbestos exposure of incident cases, through interviews. In the Emilia-Romagna region, MR was implemented in 1996 and extended its network of health professionals who report suspected mesothelioma in 2001 and 2007. Objectives: This study evaluated the impact of the extension of the network on MR sensitivity and timeliness. Methods: Mesothelioma cases were analysed in three subsequent periods: 1996-2001 (before any network extension), 2002-2007 (after first extension) and 2008-2014 (after second extension). Sensitivity was evaluated by the proportion of cases directly reported by the network out of the total number of incident cases; reporting and interview timeliness were assessed by median times between diagnosis and, respectively, reporting and interview. Pleural mesothelioma reporting timeliness was also evaluated by use of quantile regression models, stratified by diagnostic certainty and adjusted by sex and age. Results: Sensitivity increased from 79.4% (1996-2001), to 89.0% (2002-2007) and to 91.4% (2008-2013). For mesothelioma with diagnostic certainty, we recorded considerably reduced reporting times from the 50th percentile on, whereas for uncertain mesothelioma relevant reductions were observed also in the lower percentiles. A reduced time to interview was observed too, which was more significant for uncertain cases. The proportion of patients directly interviewed increased from 33.5% (1996-2001), to 39.1% (2002-2007), to 49.5% (2008-2014). Conclusions: The extended network improved the MR sensitivity and allowed shorter reporting and interview times and more frequent patient interviews, thus improving accuracy of exposure definition.